Tenant perspectives on the implementation of the community homes for opportunity: a focused ethnographic study in Southwestern Ontario - Cheryl Forchuk; Sebastian Gyamfi; Heba Hassan; Bryanna Lucyk; Richard Booth (BMC, 2023)
Abstract Background Recovery-oriented programs provide individuals with opportunities for well-being through community integration processes that enhance the degree to which individuals could live, work, and recreate in their community. The current evaluation assessed how tenants experience their home environment after the modernization of Homes for Special Care (HSC) to Community Homes for Opportunity (CHO) in Southwest Ontario, Canada. Our study identifies existing policies and practices that could interfere with or promote the modernization process. Methods We applied ethnographic qualitative techniques to purposefully recruit 188 participants with severe mental illness from 28 group homes. Focus groups were conducted at three time points, i.e., at pre-implementation/Baseline/Time I - spring 2018; Transition/Time II - fall 2018, and Final/Time III - winter 2019. Results Study findings suggest that the transition of HSC to CHO supports activities that empower tenants towards personal growth and development. Participants were largely satisfied with the support they were getting in relation to the program-related services. Tenants disclosed that their quality of life and well-being had been enhanced through participating in the program, and that their social interaction and support for each other had also improved. Most tenants demonstrated autonomy in terms of personal and financial independence. The enhanced financial support for tenants did not only improve their quality of life, but also helped to raise their purchasing power, decision making, sense of responsibility and accountability towards healthy spending of their resources. Despite tenants' good impression about the CHO, some still encountered problems and provided suggestions to further improve the program. Conclusion It is expected that a more effective and expanded CHO will lead to tenant empowerment and successful social integration.